S-100β protein in patients with severe sepsis - Vučeljić Marina; Šurbatović Maja; Vujanić Svetlana (Journal of Medical Biochemistry, 2009)
The effects of sepsis on the brain are not fully elucidated. This study investigated the serum levels of S100β protein in severe sepsis, as a biomarker of brain damage. The aim was to determine whether the levels of S100β are increased early, at the onset of sepsis, and if this protein is a good early predictor of outcome. We studied 30 patients with severe sepsis, divided into the survivors (n=8) and norsurvivors (n=22). Blood was sampled within the first 24h after the onset of symptoms. The concentrations of S100β were measured using an electrochemiluminiscence immunoassay (Elecsys 2010, Roche Diagnostics). Also, we measured the levels of C-reactive protein (CRP) using the immunonephelometric assay. Out of 30 patients, 74.4% had increased levels of S100β, while 25.6% had values within the reference range. A total of 30 patients had increased levels of CRP. The mean values of S100β and CRP did not differ significantly between the survivors and nonsurvivors (0.390±0.515 vs. 0.415± 0.508 mg/L; 98.76±69.94 vs. 161.68±118.38 mg/L). Correlation between S100β and outcome was not found. The increased levels of S100β indicate possible occult diffuse brain injury, that can be reversible. Moreover, the study showed S100β protein not to be a good early predictor of outcome in severe sepsis.